Pembentukan Akhlakul Karimah Remaja Muslim Desa Purworejo dalam Konteks Kesadaran Beragama - Ayu Lestari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Purworejo village has its own uniqueness regarding the daily lives of Muslim teenagers in it. The idealism of daily patterns with full ethics shows the success of learning patterns in them. Words and actions in everyday life that are tied to ethics are interesting to review.The work is in the form of field research, using qualitative methods, a phenomenological approach, along with data triangulation, trying to find patterns of effective learning in the village. With a focus on a) the process of forming al-karimah morals in the context of religious awareness, b) identification of moral awareness in a religious context, c) the role of various elements in successful learning.The results of the research are a) the process of forming morals in religious awareness is to use a pattern of forming awareness by involving various parties, b) the success of formation is by having an ideal pattern of behavior, both in ethics and enthusiasm for learning, c) there are three important elements that play a role in this process, namely teachers/figures, parents, and also the community